65.4k views
2 votes
Solve the initial value problem dydx=(x−2)(y−10),y(0)=5dydx=(x−2)(y−10),y(0)=5.

y=

User Leone
by
4.7k points

1 Answer

2 votes

Answer:

The solution for the initial value problem is:


y(x) = -5e^{(x^(2))/(2) - 2x} + 10

Explanation:

We have the following initial value problem:


(dy)/(dx) = (x-2)(y-10)

The first step is solving the differential equation. We can do this by the variable separation method. It means that every term with y in on one side of the equality, every term with x on the other side. So:


(dy)/(dx) = (x-2)(y-10)


(dy)/(y-10) = (x-2)dx

To find y in function of x, we integrate both sides.


(dy)/(y-10) = (x-2)dx


\int {(1)/(y-10)} \, dy = \int {(x-2)} \, dx

Solving each integral separately


\int {(1)/(y-10)} \, dy

This one we solve by substitution


u = y-10, du = dy


\int {(1)/(y-10)} \, dy = \int {(1)/(u)} \, du = ln(u) = ln((y-10))


\int {(x-2)} \, dx = (x^(2))/(2) - 2x + K

Now we have that:


\int {(1)/(y-10)} \, dy = \int {(x-2)} \, dx


\ln{(y-10) = (x^(2))/(2) - 2x + K}

To solve for y, we apply the exponential to both sides, since the exponential and ln are inverse operations:


e^{ln((y-10)) = e^{(x^(2))/(2) - 2x + K}


y - 10 = Ke^{(x^(2))/(2) - 2x}


y(x) = Ke^{(x^(2))/(2) - 2x} + 10


y(0) = 5 means that when
x = 0, y(x) = 5. So:


5 = Ke^{(0^(2))/(2) - 2*0} + 10


Ke^(0) = -5


K = -5

So, the solution for the initial value problem is:


y(x) = -5e^{(x^(2))/(2) - 2x} + 10

User Nethero
by
4.3k points